Herbal smoke, aerosol and cologne may play a role as disinfectant against the COVID-9 battle - Saara Ahmad Muddasir Khan; Asra Khan; Abdul Mannan Baig (Journal of the Pakistan Medical Association, 2022)
Its letter to the editor